x+0.20(3)=0.60(x+3)

Simple and best practice solution for x+0.20(3)=0.60(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+0.20(3)=0.60(x+3) equation:


Simplifying
x + 0.20(3) = 0.60(x + 3)

Multiply 0.20 * 3
x + 0.6 = 0.60(x + 3)

Reorder the terms:
0.6 + x = 0.60(x + 3)

Reorder the terms:
0.6 + x = 0.60(3 + x)
0.6 + x = (3 * 0.60 + x * 0.60)
0.6 + x = (1.8 + 0.60x)

Solving
0.6 + x = 1.8 + 0.60x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.60x' to each side of the equation.
0.6 + x + -0.60x = 1.8 + 0.60x + -0.60x

Combine like terms: x + -0.60x = 0.4x
0.6 + 0.4x = 1.8 + 0.60x + -0.60x

Combine like terms: 0.60x + -0.60x = 0.00
0.6 + 0.4x = 1.8 + 0.00
0.6 + 0.4x = 1.8

Add '-0.6' to each side of the equation.
0.6 + -0.6 + 0.4x = 1.8 + -0.6

Combine like terms: 0.6 + -0.6 = 0.0
0.0 + 0.4x = 1.8 + -0.6
0.4x = 1.8 + -0.6

Combine like terms: 1.8 + -0.6 = 1.2
0.4x = 1.2

Divide each side by '0.4'.
x = 3

Simplifying
x = 3

See similar equations:

| 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 | | 3(6+8R)-3(R+2)= | | 4k^2+26k-36=0 | | -5=x-9 | | 4(x+8)=-4(x-16) | | -0.01x^2+0.92x=0 | | 5e+10=25 | | -6=n+2+7n | | 3x+2x+3+3x+2x+3=5x-3+5x-3+5x-3 | | x+4/2=5/2-x-1/5 | | -4=8w-12 | | 10x+7+3x=0 | | 73-3x=10x-21 | | 8x+5=5x+7 | | -14=a+(-23) | | 2=19+d | | 6y+9=12 | | 8x^2+4y-32=0 | | 6x+65=9x-7 | | 8(3x/8-1)=8(5/8) | | 8-3c=2c+8 | | c=dpi |

Equations solver categories